Physical Exercise and Fitness Level Are Related to Cognitive and Psychosocial Functioning in Adolescents - Reigal, Rafael Enrique; Hernández-Mendo, Antonio; Juárez-Ruiz de Mier, Rocío; Morales-Sánchez, Verónica (Frontiers in Psychology, 2020)
The purpose of this study was to analyze how physical activity and fitness are related to cognitive and psychosocial functioning in adolescents. A total of 208 adolescents aged between 14 and 16 years from the city of Malaga participated. This is a comparative and predictive study. The instruments used for the evaluation were the Tanita® BC-601 Body Composition Monitor, the Eurofit Physical Condition Test Battery, the D2 Test of Attention, the WISC-IV Symbol Search and Coding tests, the General Self-Efficacy Scale (GSE), the General Health Questionnaire (GHQ-28), and the Satisfaction with Life Scale (SWLS). The results indicated that adolescents who practiced more hours of physical activity per week and were in better physical condition achieved higher scores in the set of tests analyzed. In addition, cardiorespiratory fitness was the physical fitness variable most closely related to and predictive of cognitive and psychosocial functioning. The data suggest that engaging in physical activity in adolescence may be appropriate to improve health and well-being, contributing to better development at this stage.